Implementation of the Drill Method Using the High Lob Throw to Improve 7-Meter Pointing Results for Petanque Athletes - Uswatun Hassanah; Donni Pestalozi; Adika Fatahilah (CV. Edujavare Publishing, 2026)
This study aimed to determine the effect of applying the drill training method using high lob throws on improving the 7 meter pointing performance of pétanque athletes from Musi Rawas Regency. This research employed a quantitative approach with a quasi experimental design using a one-group pre-test and post-test design. Data were analyzed using the Shapiro-wilk normality test and the paired sample t-test with SPSS version 25. The results indicated that the data were normally distributed, with significance values of 0.125 for the pre-test and 0.172 for the post-test (Sig.> 0.05) the hypothesis test showed a t-value of 21-879 with a Sig. (2-tailed) value of 0.000 (<0.05), indicating that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. The traning program also improved athletes’motor skills through the development of muscle memory, better control of throwing force, greater accuracy of ball trajectory and landing point, as well as enhanced focus concentrarion, emotional stability, and self-confidence. Therefore, the drill training method using high lob throws was proven to be effective in improving the 7 meter pointing athletes from Musi Rawas Regency.